2019
DOI: 10.1016/j.kint.2018.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid treatment exacerbates nephrotic syndrome in a zebrafish model of magi2a knockout

Abstract: Recently, recessive mutations of MAGI2 were identified as a cause of steroid-resistant nephrotic syndrome (SRNS) in humans and mice. To further delineate the pathogenesis of MAGI2 loss of function, we generated stable knockout lines for the two zebrafish orthologues magi2a and magi2b by CRISPR/Cas9. We also developed a novel assay for the direct detection of proteinuria in zebrafish independent of transgenic background. Whereas knockout of magi2b did not yield a nephrotic syndrome phenotype, magi2a -/larvae de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…At 8 dpf, a little more than 50% of nphs1-/- developed periorbital edema, and by 10 dpf, more than 95% of the mutants had severe peri-orbital edema ( Figure 1G ). Thus, nphs1-/- displayed edematous phenotypes, resembling other zebrafish models of podocyte defects ( Wan et al, 2016 ; Jobst-Schwan et al, 2019 ) and reminiscent of edema seen in pediatric patients with NS. This progressed into severe whole-body edema and lethality occurred around 2 weeks of age ( Supplementary Figure S2C ), similar to Nephrin KO mice that are lethal shortly after birth.…”
Section: Resultsmentioning
confidence: 57%
“…At 8 dpf, a little more than 50% of nphs1-/- developed periorbital edema, and by 10 dpf, more than 95% of the mutants had severe peri-orbital edema ( Figure 1G ). Thus, nphs1-/- displayed edematous phenotypes, resembling other zebrafish models of podocyte defects ( Wan et al, 2016 ; Jobst-Schwan et al, 2019 ) and reminiscent of edema seen in pediatric patients with NS. This progressed into severe whole-body edema and lethality occurred around 2 weeks of age ( Supplementary Figure S2C ), similar to Nephrin KO mice that are lethal shortly after birth.…”
Section: Resultsmentioning
confidence: 57%
“…Previous studies have reported that corticosteroids can induce PKD in mammalian models ( McDonald et al, 1990 ). Based on this, we tested whether stk3 −/− mutants were sensitive to treatments with corticosteroid agonists, dexamethasone and prednisolone, and the doses of treatments were as used in a previous study ( Jobst-Schwan et al, 2019 ). The results showed that dexamethasone treatment aggravated the edema phenotype in stk3 −/− mutants in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Regrettably, due to long-term treatment of LN, steroid resistance and concurrent infections are often induced, thus making treatment more challenging. The alternative use of other cytotoxic agents remains risky and challenging and is further complicated by the reduced efficacy of other immunosuppressive agents when steroid resistance occurs (Jobst-Schwan et al, 2019). Thus, developing an understanding of how steroid resistance can be reversed in LN is vital.…”
Section: Introductionmentioning
confidence: 99%